The Frontiers of Applied Demography - Swanson, David A. (Springer International Publishing : Imprint: Springer, 2017)
This book details cutting-edge methods and findings that may shape the future of applied demography. Inside, readers will discover new insights into the databases, substantive issues, and methodological approaches that can help them to improve how they use demography in decision making and planning problems in both public and private settings. The topics and perspectives are found in the book's 23 chapters, which are organized into three major sections: (I) Demographic Information for Decision-Making: Case Studies; (II) Data: Issues and Analyses; and (III) Projection and Estimation Methods: Evaluations, Examples, and Discussions. Coverage includes chapters on migration, demographic market analysis, future courtroom needs, trends in the needs of the elderly, access to health care, longitudinal data systems, census costs, and new approaches to small area estimation and projection methods. The case studies represent a wide range of countries, including Australia, Canada, China, England, India, Japan, and the United States of America. Overall, this edited volume collects papers that were presented at different conferences, including the 8th international conference on population geographies (University of Queensland, 2015), the 2014 Applied Demography Conference (San Antonio, Texas, USA), and the annual conference of the Canadian Population Society. Applied demography touches many aspects of our lives and its practitioners continue to push methodological and empirical boundaries. This book documents the steady evolution of this field. It shows demographers, sociologists, economists, planners, marketers, and others how they can improve the quality and relevance of demographic information now and in the future.
Keywords: Social sciences.; Public health.; Statistics.; Aging.; Emigration and immigration.; Demography.; elektronické knihy; electronic books